'Our culture prohibits some things': qualitative inquiry into how sociocultural context influences the scale-up of community-based injectable contraceptives in Nigeria. Issue 7 (19th July 2020) - Akinyemi, Oluwaseun Oladapo; Harris, Bronwyn; Kawonga, Mary
Abstract : Objectives: To explore how sociocultural factors may support or impede the adoption of community-based distribution of injectable contraceptives in Nigeria. Design: A qualitative study based on inductive thematic analysis was conducted through in-depth interviews and focus group discussions. Setting: Most participants lived in Gombe State, North-East Nigeria. Other participants were from Ibadan (South-West) and Abuja (Federal Capital Territory). Participants: Through seven key informant interviews, 15 in-depth interviews and 10 focus group discussions, 102 participants were involved in the study. Methods: This study conducted in 2016 was part of a larger study on scale-up of community-based distribution of injectable contraceptives. Qualitative data were collected from traditional and religious leaders, health workers and community members. The data were audio recorded, transcribed and analysed using a thematic framework method. Results: Sociocultural challenges to scale-up included patriarchy and men's fear of losing control over their spouses, traditional and religious beliefs about fertility, and myths about contraceptives and family planning. As a result of deep-rooted beliefs that children are 'divine blessings' and that procreation should not be regulated, participants described a subtle resistance to uptake of injectable contraceptives. Since Gombe is largely a patriarchal society, male involvement emerged as important to the success of meaningful innovation uptake. Community leaders largely described their participation in the scale-up process as active, although they also identified the scope for further involvement and recognition. Conclusion: Scale-up is more than setting up health sector implementing structures, training health workers and getting innovation supplies, but also requires preparedness which includes paying attention to complex contextual issues. Policy implementers should also see scale-up as a learning process and be willing to move at the speed of the community.